Pengaruh Jenis Katalis pada Elektroda Pembanding terhadap Efisiensi Dye Sensitized Solar Cells dengan Klorofil sebagai Dye Sensitizer: Nurrisma Puspitasari, Siti Rabiatul Adawiyah, Muhammad Noer Fajar, Gatut Yudoyono, Agus Rubiyanto, Endarko - Nurrisma Puspitasari Nurrisma Puspitasari; Siti Rabiatul Adawiyah Siti Rabiatul Adawiyah; Muhammad Noer Fajar Muhammad Noer Fajar; Gatut Yudoyono Gatut Yudoyono; Agus Rubiyanto Agus Rubiyanto; Endarko Endarko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2017)
Dye-sensitized Solar Cell (DSSC) is a dye sensitized solar cells are formed by a sandwich structure where there are five parts include: glass ITO (Indium Tin Oxide) as a substrate; TiO2 as a semiconductor material; chlorophyll dye as an electron donor; electrolyte as electron transfer. Nanometer-sized TiO2 powder obtained through synthesis by coprecipitation method. Measurements were taken at the power of 100 mW/cm2. The results of the efficiency of DSSC using active carbon as a catalyst in the reference electrode, produces a larger percentage than black carbon and graphite, which is of 0.05% for active carbon, black carbon to 0.032%, 0.029% for graphite.